Revealing patterns of nocturnal migration using the European weather radar network - Nilsson, C.; Dokter, A.; Verlinden, L.; Shamoun-Baranes, J.; Schmid, B.; Desmet, P.; Bauer, S.; Chapman, J.; Alves, J.; Stepanian, P.; Sapir, N.; Wainwright, C.; et al. (Blackwell Publishing, 2018)
© 2018 The Authors Nocturnal avian migration flyways remain an elusive concept, as we have largely lacked methods to map their full extent. We used the network of European weather radars to investigate nocturnal bird movements at the scale of the European flyway. We mapped the main migration directions and showed the intensity of movement across part of Europe by extracting biological information from 70 weather radar stations from northern Scandinavia to Portugal, during the autumn migration season of 2016. On average, over the 20 nights and all sites, 389 birds passed per 1 km transect per hour. The night with highest migration intensity showed an average of 1621 birds km–1 h–1 passing the radar stations, but there was considerable geographical and temporal variation in migration intensity. The highest intensity of migration was seen in central France. The overall migration directions showed strong southwest components. Migration dynamics were strongly related to synoptic wind conditions. A wind-related mass migration event occurred immediately after a change in wind conditions, but quickly diminished even when supporting winds continued to prevail. This first continental-scale study using the European network of weather radars demonstrates the wealth of information available and its potential for investigating large-scale bird movements, with consequences for ecosystem function, nutrient transfer, human and livestock health, and civil and military aviation.